Solar oven with downward and upward solar gain for children’s dining rooms in developing countries - Esteves Miramont, Alfredo (2014)
In Argentina there exist children's dining rooms where infants and their mothers take lunch at noon and glasses of milk in the afternoon. These dining rooms are established in rural or marginal urban areas. Solar ovens are an interesting option for cooking with less expense of money, and they diminish environmental impact in these zones. A solar oven with downward and upward solar gain was built and tested. Upward solar gain is through Fresnel reflectors. The use of Fresnel reflectors resulted in higher heating power as compared to a solar oven with upper reflectors only. The performance with different numbers of Fresnel units was compared with a single-reflector solar oven with no lower Fresnel reflectors. Oven power was analysed and the result indicates that power grows as the number of Fresnel reflectors increases: it grows by 55% using 3 to 9 Fresnel reflectors, and by 34.6% with 3 to 6 Fresnel reflectors. These values are enough to cook several rations of food, and make this oven appropriate for use in dining rooms in developing countries.